Incidence of new-onset diabetes mellitus and association with mortality in childhood solid organ transplant recipients: a population-based study - Chanchlani, Rahul (Nephrol Dial Transplant, 2019)
BACKGROUND: Precise estimates of the long-term risk of new-onset diabetes and its impact on mortality among transplanted children are not known. METHODS: We conducted a cohort study comparing children undergoing solid organ (kidney, heart, liver, lung and multiple organ) transplant (n = 1020) between 1991 and 2014 with healthy non-transplanted children (n = 7 134 067) using Ontario health administrative data. Outcomes included incidence of diabetes among transplanted and non-transplanted children, the relative hazard of diabetes among solid organ transplant recipients, overall and at specific intervals posttransplant, and mortality among diabetic transplant recipients. RESULTS: During 56 019 824 person-years of follow-up, the incidence rate of diabetes was 17.8 [95% confidence interval (CI) 15–21] and 2.5 (95% CI 2.5–2.5) per 1000 person-years among transplanted and non-transplanted children, respectively. The transplant cohort had a 9-fold [hazard ratio (HR) 8.9; 95% CI 7.5–10.5] higher hazard of diabetes compared with those not transplanted. Risk was highest within the first year after transplant (HR 20.7; 95% CI 15.9–27.1), and remained elevated even at 5 and 10 years of follow-up. Lung and multiple organ recipients had a 5-fold (HR 5.4; 95% CI 3.0–9.8) higher hazard of developing diabetes compared with kidney transplant recipients. Transplant recipients with diabetes had a three times higher hazard of death compared with those who did not develop diabetes (HR 3.3; 95% CI 2.3–4.8). CONCLUSIONS: The elevated risk of diabetes in transplant recipients persists even after a decade, highlighting the importance of ongoing surveillance. Diabetes after transplantation increases the risk of mortality among childhood transplant recipients.